1997
DOI: 10.1016/s0092-8674(00)80215-9
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylases Associated with the mSin3 Corepressor Mediate Mad Transcriptional Repression

Abstract: Transcriptional repression by Mad-Max heterodimers requires interaction of Mad with the corepressors mSin3A/B. Sin3p, the S. cerevisiae homolog of mSin3, functions in the same pathway as Rpd3p, a protein related to two recently identified mammalian histone deacetylases, HDAC1 and HDAC2. Here, we demonstrate that mSin3A and HDAC1/2 are associated in vivo. HDAC2 binding requires a conserved region of mSin3A capable of mediating transcriptional repression. In addition, Mad1 forms a complex with mSin3 and HDAC2 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
736
2

Year Published

1998
1998
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 895 publications
(767 citation statements)
references
References 43 publications
(17 reference statements)
29
736
2
Order By: Relevance
“…The function of each of the MAD transcriptional repressors in the ®ne tuning of the transition between proliferation and di erentiation might actually be identical. Each would downregulate the same set of target genes by recruiting mSIN3-histone deacetylase complexes into gene regulatory regions (Alland et al, 1997;Hassig et al, 1997;Laherty et al, 1997). Alternatively the four Mad family members may di er functionally in terms of DNA binding a nity or speci®city, or strength and mode of transcriptional repression in ways that have not yet been detected in the biochemical or biological assays carried out thus far.…”
Section: Mad Protein Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of each of the MAD transcriptional repressors in the ®ne tuning of the transition between proliferation and di erentiation might actually be identical. Each would downregulate the same set of target genes by recruiting mSIN3-histone deacetylase complexes into gene regulatory regions (Alland et al, 1997;Hassig et al, 1997;Laherty et al, 1997). Alternatively the four Mad family members may di er functionally in terms of DNA binding a nity or speci®city, or strength and mode of transcriptional repression in ways that have not yet been detected in the biochemical or biological assays carried out thus far.…”
Section: Mad Protein Functionmentioning
confidence: 99%
“…MAD ± MAX heterodimers appear to recruit a complex containing mSIN3 and the histone-deacetylases HDAC1 or HDAC2. This has led to the proposal that modi®cation of chromatin into a repressive structure by deacetylation of histones is responsible for MAD-and MNT-mediated transcriptional repression (Alland et al, 1997;Hassig et al, 1997;Laherty et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed SMRT and N-CoR interact strongly with unliganded receptors and are released upon ligand binding. A series of recent reports (Alland et al, 1997;Hassig et al, 1997;Heinzel et al, 1997;Kadosh and Struhl, 1997;Laherty et al, 1997;Zhang et al, 1997) have shown that SMRT/ N-CoR co-repressors are part of a multiprotein complex including the Mad co-repressors mSin3A and B (Ayer et al, 1995;Schreiber-Agus et al, 1995) and the histone deacetylases HDAC1/HD1 and HDAC2/mRPD3 (Taunton et al, 1996;Yang et al, 1996). These studies, that strengthen the major role of histone acetylation/deacetylation in transcriptional regulation, provide the basis for the existence of a common repression pathway between nuclear receptors and basic region-helix ± loop ± helix-leucine zipper (bHLH-Zip) proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The Mad family proteins (Ayer et al, 1993;Zervos et al, 1993;Hurlin et al, 1995), among which Mxi1, can antagonize Myc by interacting with Max. This complex recruits Sin3A or Sin3B transcriptional repressors, the co-repressor N-CoR, and the histone deacetylase HDAC1 (Schreiber-Agus et al, 1995;Rao et al, 1996;Alland et al, 1997;Hassig et al, 1997;Laherty et al, 1997). Direct repression of the c-Myc promoter by Mxi1 can also take place (Lee and Ziff, 1999).…”
mentioning
confidence: 99%